Technology and communication: In the Space of Public Policy - Ravichander, Dr. Annapoorana (IIPA Digest)
In a world full of challenges and sometimes confusion, the use of technology and communication plays a major role, especially in public policies. To elaborate," technology is the application of conceptual knowledge for achieving practical goals, especially in a reproducible way'. - Reproduced